2019
DOI: 10.1136/bmjopen-2018-027212
|View full text |Cite
|
Sign up to set email alerts
|

Associations between anthropometric indicators and both refraction and ocular biometrics in a cross-sectional study of Chinese schoolchildren

Abstract: ObjectiveTo identify associations between anthropometric indicators (height, weight and body mass index (BMI)) and both refraction and ocular biometrics in Chinese schoolchildren in Tianjin, China.DesignCross-sectional study.ParticipantsA total of 482 (86.07%) students (6–15 years old) with no history of ocular or systemic pathologies were enrolled in this study.MethodologyHeight and weight were measured using standardised protocols. Ocular biometrics (axial length (AL), vitreous chamber depth (VCD) and cornea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 31 publications
3
20
1
Order By: Relevance
“…But BMI did not raise the risk of myopia. The current results are consistent with Ye et al, 14 who demonstrated that among 482 Chinese children aged between 6 ~ 15 years, taller individuals were associated with longer ALs (b=+0.25, p<0.01), deeper VCDs (b=+0.23, p<0.01), higher AL/CC ratios (b=+0.04, p<0.01) and more negative refractions (b=−0.48, p<0.01). Nonetheless, BMI was not correlated with refraction in their multiple linear regression models.…”
Section: Discussionsupporting
confidence: 92%
“…But BMI did not raise the risk of myopia. The current results are consistent with Ye et al, 14 who demonstrated that among 482 Chinese children aged between 6 ~ 15 years, taller individuals were associated with longer ALs (b=+0.25, p<0.01), deeper VCDs (b=+0.23, p<0.01), higher AL/CC ratios (b=+0.04, p<0.01) and more negative refractions (b=−0.48, p<0.01). Nonetheless, BMI was not correlated with refraction in their multiple linear regression models.…”
Section: Discussionsupporting
confidence: 92%
“…We found no correlation between baseline physical parameters and future SE, which is consistent with the Growing Up in Singapore Towards Healthy Outcomes (GUSTO) birth cohort study in Singapore [ 14 ]. Conversely, Ye S et al found that personal anthropometry values, such as height and weight, remained independently related to refraction among schoolchildren aged 6–15 years old in Tianjin, China [ 38 ]. We infer that the absence of a relationship between anthropometric measures and SE may be due to the difference in the study population that varies in corneal and lens powers, which compensate for AL growth, although the eye grows in harmony with the body.…”
Section: Discussionmentioning
confidence: 99%
“…The association between height and AL has been demonstrated in previous cross-sectional studies (11)(12)(13)(14) and longitudinal cohort studies (15)(16)(17). In 2002, Saw et al (11) proved that taller children have longer AL by analyzing the height and AL of 1,449 children aged 7-9 years.…”
Section: Introductionmentioning
confidence: 86%
“…AL was measured using non-invasive, non-contact optical low-coherence reflectometry (Lenstar LS900; Haag-Streit AG, 3098 Koeniz, Switzerland) without pupil dilation. Three consecutive measurements were acquired, and the mean result was used ( 13 ). If the error of the three measurements was >0.1 mm, AL was remeasured.…”
Section: Methodsmentioning
confidence: 99%